Epitope Mapping of Antibodies to Alpha-Synuclein in LRRK2 Mutation Carriers, Idiopathic Parkinson Disease Patients, and Healthy Controls - Alvarez-Castelao, Beatriz; Gorostidi, Ana; Ruíz-Martínez, Javier; López de Munain, Adolfo; Castaño, José G. (Frontiers in Aging Neuroscience, 2014)
Alpha-synuclein (Snca) plays a major role in Parkinson Disease (PD). Circulating anti-Snca antibodies have been described in PD patients and healthy controls, but they have been poorly characterized. This study was designed to assess the prevalence of anti-Snca reactivity in human subjects carrying the LRRK2 mutation, idiopathic PD (iPD) patients and healthy controls and to map the epitopes of the anti-Snca antibodies. Antibodies to Snca were detected by ELISA and immunoblotting using purified recombinant Snca in plasma from individuals carrying LRRK2 mutations (104), iPD patients (59) and healthy controls (83). Epitopes of antibodies were mapped using recombinant protein constructs comprising different regions of Snca. Clear positive anti-Snca reactivity showed no correlation with age, sex, years of evolution or the disability scores for PD patients and anti-Snca reactivity was not prevalent in human patients with other neurological or autoimmune diseases. Thirteen of the positive individuals were carriers of LRRK2 mutations either non-manifesting (8 out 49 screened) or manifesting (5 positive out 55), three positive (out of 59) were iPD patients and five positive (out of 83) were healthy controls. Epitope mapping showed that antibodies against the N-terminal (a.a. 1-60) or C-terminal (a.a. 109-140) regions of Snca predominate in LRRK2 mutation carriers and iPD patients, being N122 a critical aminoacid for recognition by the anti-C-terminal directed antibodies. Anti-Snca circulating antibodies seem to cluster within families carrying the LRRK2 mutation indicating possible genetic or common environmental factors in the generation of anti-Snca antibodies. These results suggest that case-controls studies are insufficient and further studies in family cohorts of patients and healthy controls should be undertaken, to progress in the understanding of the possible relationship of anti-Snca antibodies and PD pathology.